Solid electrolyte material and method for producing same
By using amorphous solid electrolyte materials containing Li, Ti and F in solid-state batteries, the problem of poor bonding reliability of Li2TiF6 is solved, and a high-performance solid electrolyte material is realized, which improves the ionic conductivity and charge and discharge characteristics of the battery. .
Patent Information
- Application Number
- CN202380041119.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-04-17
- Publication Date
- 2025-01-07
AI Technical Summary
The powder pressing tissue bonding reliability of Li2TiF6 in existing solid-state batteries is poor, making it difficult to achieve practical conductivity, and the prior art is difficult to provide high-performance solid electrolyte materials.
Using amorphous solid electrolyte material containing Li, Ti and F, the crystal phase compounds containing Li, Ti and F are synthesized and disturbed, and the amorphous structure with high ionic conductivity is formed, and the particle deformation and bonding interface formation is optimized. sex.
High ionic conductivity and excellent charging and discharging characteristics are achieved, and the performance and reliability of the battery are improved, especially in all-solid-state batteries, which show high conductivity and stability.
Smart Images

Figure CN119278489A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to solid electrolyte materials and methods for making the same. Background Art
[0002] Patent Document 1 discloses an electrode active material represented by Li2TiF6.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-238687 Summary of the invention
[0006] Problems to be solved by the invention
[0007] An object of the present disclosure is to provide a novel solid electrolyte material with high usefulness.
[0008] Means for solving problems
[0009] The solid electrolyte material disclosed herein is a solid electrolyte material containing Li, Ti, and F, which contains an amorphous substance containing Li, Ti, and F.
[0010] Effects of the Invention
[0011] The present disclosure can provide a novel solid electrolyte material with high usefulness. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a flowchart showing an example of the manufacturing method according to the second embodiment.
[0013] Figure 2 It is a graph showing the X-ray diffraction patterns of Samples 4 to 7. DETAILED DESCRIPTION
[0014] (Overview of one aspect of the present disclosure)
[0015] The solid electrolyte material of the first aspect of the present disclosure is a solid electrolyte material containing Li, Ti, and F, and contains an amorphous substance containing Li, Ti, and F.
[0016] The solid electrolyte material of the first embodiment has practical ion conductivity because it contains an amorphous material containing Li, Ti and F. In addition, the solid electrolyte material of the first embodiment is excellent in particle deformability suitable for a pressed powder structure and bonding interface formation. Therefore, according to the first embodiment, a new solid electrolyte material with high usefulness can be realized.
[0017] In the second aspect of the present disclosure, for example, the solid electrolyte material of the first aspect may be a solid solution.
[0018] According to the second aspect, a novel solid electrolyte material with high usefulness can be realized.
[0019] In the third embodiment of the present disclosure, for example, with respect to the solid electrolyte material of the first or second embodiment, it may be that, in the X-ray diffraction pattern obtained by powder X-ray diffraction measurement of the solid electrolyte material, there is at least one peak in each of the first range where the diffraction angle 2θ is greater than 20° and less than 22°, the second range where the diffraction angle 2θ is greater than 40° and less than 42°, and the third range where the diffraction angle 2θ is greater than 26° and less than 28°, and the half-width of the strongest peak in the first range is greater than 1°.
[0020] According to the third aspect, a novel solid electrolyte material with high usefulness can be realized.
[0021] In the fourth embodiment of the present disclosure, for example, with respect to the solid electrolyte material of any one of the first to third embodiments, it may be that the strongest peak in the first range has a higher intensity than the strongest peak in the second range, and the strongest peak in the second range has a higher intensity than the strongest peak in the third range.
[0022] According to the fourth aspect, the solid electrolyte material has high ion conductivity.
[0023] In a fifth aspect of the present disclosure, for example, the solid electrolyte material of any one of the first to fourth aspects may be in a particle form.
[0024] According to the fifth aspect, when used for a battery or the like, a battery having excellent charge and discharge characteristics can be realized.
[0025] In a sixth aspect of the present disclosure, for example, with respect to the solid electrolyte material of any one of the first to fifth aspects, the crystallinity of the surface of the solid electrolyte material may be lower than the crystallinity of the central portion of the solid electrolyte material.
[0026] According to the sixth aspect, high ion conductivity can be achieved when a compressed powder structure is formed.
[0027] In a seventh aspect of the present disclosure, for example, the solid electrolyte material of any one of the first to sixth aspects may further contain at least one selected from the group consisting of Ni, Mo, Cr, Fe, and ZrO 2 .
[0028] According to the seventh embodiment, a new solid electrolyte material with high usefulness can be realized.
[0029] In an eighth aspect of the present disclosure, for example, the solid electrolyte material according to any one of the first to sixth aspects may further contain a crystal phase containing Li, Ti, and F.
[0030] According to the eighth aspect, by making the crystal contain an amorphous structure, a solid electrolyte material having high ion conductivity can be realized.
[0031] In a ninth aspect of the present disclosure, for example, in the solid electrolyte material of the eighth aspect, the crystal phase may contain a tetragonal crystal.
[0032] According to the ninth aspect, the solid electrolyte material has high ion conductivity.
[0033] A method for producing a solid electrolyte material according to a tenth aspect of the present disclosure includes: (A) synthesizing a compound containing a crystal phase containing Li, Ti, and F; and (B) performing a treatment for disturbing crystals of the compound.
[0034] According to the tenth embodiment, a new solid electrolyte material with high usefulness can be realized.
[0035] In the eleventh aspect of the present disclosure, for example, in the production method of the tenth aspect, in the (A), the compound may be synthesized by calcining a mixture of raw materials.
[0036] According to the eleventh aspect, a solid electrolyte material having high ion conductivity can be produced.
[0037] In a twelfth aspect of the present disclosure, for example, in the production method of the eleventh aspect, in the calcination, the mass change rate of the compound before and after the calcination may be 1% or less.
[0038] According to the twelfth embodiment, a uniform compound can be synthesized, and a solid electrolyte material having higher ion conductivity can be manufactured.
[0039] In a thirteenth aspect of the present disclosure, for example, in the production method of any one of the tenth to twelfth aspects, in the (B), the compound may be subjected to a mechanochemical treatment.
[0040] According to the thirteenth aspect, a solid electrolyte material having high ion conductivity can be produced.
[0041] In a fourteenth aspect of the present disclosure, for example, in the production method of the thirteenth aspect, the mechanochemical treatment may be ball milling.
[0042] According to the fourteenth aspect, a solid electrolyte material having higher ion conductivity can be produced.
[0043] The following describes embodiments of the present disclosure. The present disclosure is not limited to the following embodiments.
[0044] (First Embodiment)
[0045] The solid electrolyte material of the first embodiment is a solid electrolyte material containing Li, Ti, and F, and contains an amorphous substance containing Li, Ti, and F.
[0046] The solid electrolyte material of the first embodiment has practical ion conductivity, for example, high ion conductivity, because it contains amorphous materials, and is excellent in particle deformability and bonding interface formation, particularly suitable for a compacted powder structure.
[0047] In the present disclosure, “high ion conductivity” refers to relatively high ion conductivity when solid electrolyte materials formed of the same element are compared with each other. The solid electrolyte material of the first embodiment can have an ion conductivity of 0.5 μS / cm or more at around room temperature, for example.
[0048] The term "amorphous" in the present disclosure includes a substance having an amorphous structure and a deformed crystal structure, that is, a substance having a disordered crystal structure. The fact that the solid electrolyte material of the first embodiment contains an amorphous substance can be confirmed by an X-ray diffraction pattern obtained by X-ray diffraction measurement. The X-ray diffraction pattern can be measured using Cu-Kα rays (wavelength and ) as an X-ray source, and measured by the θ-2θ method. In addition, the fact that the solid electrolyte material of the first embodiment contains amorphous materials can also be confirmed using a transmission electron microscope (TEM).
[0049] For example, the half-peak width of the maximum peak in the X-ray diffraction pattern obtained by X-ray diffraction measurement of a substance having an amorphous structure is 1° or more. In addition, the region with a deformed crystal structure, that is, the region with disordered crystallinity can be confirmed by TEM. In the case of amorphous, since the lattice image cannot be seen under TEM, the region with a deformed crystal structure, that is, the region with disordered crystallinity can be observed as an image of a region with high order and a region where the lattice image cannot be seen in the crystal region, that is, the disordered region. Therefore, for a substance having a deformed crystal structure, that is, a disordered crystal structure, a region where the lattice image cannot be seen in the crystal region under TEM can be observed. Therefore, in this embodiment, "amorphous containing Li, Ti and F" means that, for example, in the X-ray diffraction pattern obtained by X-ray diffraction measurement, the half-peak width of the maximum peak in the range of diffraction angle 2θ of 20° or more and 22° or less is 1° or more; or, for example, a compound containing Li, Ti and F is observed in a region where the lattice image cannot be seen in the crystal region under TEM.
[0050] The solid electrolyte material of the first embodiment can be used to obtain a battery having excellent charge and discharge characteristics. An example of the battery is an all-solid-state battery. The battery can be a primary battery or a secondary battery.
[0051] The solid electrolyte material of the first embodiment may be a solid solution. According to the above configuration, the solid electrolyte material has high electrical conductivity. In addition, high ion conductivity can be achieved in the pressed powder structure. In the present disclosure, the solid solution refers to, for example, a single-phase solid.
[0052] In the X-ray diffraction pattern obtained by powder X-ray diffraction measurement of the solid electrolyte material, at least one peak may exist in each of the first range of the diffraction angle 2θ value of 20° to 22°, the second range of the diffraction angle 2θ value of 40° to 42°, and the third range of the diffraction angle 2θ value of 26° to 28°, and the half-peak width of the strongest peak in the first range may be 1° or more. According to the above configuration, the solid electrolyte material has high ionic conductivity.
[0053] In the above X-ray diffraction pattern, the strongest peak in the first range may have a higher intensity than the strongest peak in the second range, and the strongest peak in the second range may have a higher intensity than the strongest peak in the third range. According to the above configuration, the solid electrolyte material has high ion conductivity.
[0054] The solid electrolyte material may further contain a crystalline phase. The solid electrolyte material may further contain a crystalline phase containing Li, Ti and F. The crystalline phase may contain a tetragonal crystal. The crystalline phase may be a tetragonal crystal. By making the tetragonal crystal contain an amorphous structure, high ionic conductivity can be imparted. According to the above composition, a solid electrolyte material with high ionic conductivity can be realized. The constituent elements of the amorphous and crystalline phases in the solid electrolyte material may be the same as each other.
[0055] The solid electrolyte material of the first embodiment may be in a particle form. Thus, in the pressed powder structure, the soft particles containing amorphous low crystallinity firmly form a bonding interface. Therefore, the solid electrolyte material of the first embodiment can realize a battery with excellent charge and discharge characteristics, for example.
[0056] When the solid electrolyte material of the first embodiment is in the form of particles, the crystallinity of the surface of the particles can be lower than that of the central part of the particles. As a result, the surface of the particles becomes a soft state with higher conductivity and excellent plasticity than the inside of the particles. As a result, in the compacted structure, the bonding property between the particles is improved, the resistance at the bonding interface is particularly reduced, and an ionic conduction path between the particles is continuously formed. In addition, peeling between the particles that can be caused by thermal cycling can be suppressed. That is, high bonding reliability is obtained. As described above, the solid electrolyte material of the first embodiment can realize a compacted structure with excellent reliability and high ionic conductivity. Therefore, a high-performance battery can be realized using the solid electrolyte material of the first embodiment. The difference in crystallinity can be confirmed, for example, by observing the disorder of the lattice arrangement using a high-resolution TEM or scanning transmission electron microscope (STEM) capable of observing lattice images.
[0057] In the solid electrolyte material of the first embodiment, the composition ratios of Li, Ti, and F may not be stoichiometric composition ratios. The solid electrolyte material of the first embodiment may also contain a compound represented by the composition formula of 1-a Ti a F (1+3a) . Here, 0 < a < 1 and 0 < b < 1 are satisfied. The solid electrolyte material of the first embodiment may contain a compound represented by the composition formula of Li2TiF6.
[0058] The solid electrolyte material of the first embodiment may also contain elements other than Li, Ti, and F.
[0059] The solid electrolyte material of the first embodiment may further contain at least one selected from the group consisting of Ni, Mo, Cr, Fe, and ZrO2.
[0060] The solid electrolyte material of the first embodiment may further contain at least one selected from the group consisting of Fe, Cr, and ZrO2.
[0061] The solid electrolyte material of the first embodiment may also consist essentially of Li, Ti, and F. Here, "the solid electrolyte material consists essentially of Li, Ti, and F" means that the sum of the amounts of substance of Li, Ti, and F relative to the sum of the amounts of substance of all elements constituting the solid electrolyte material of the first embodiment (i.e., the mole fraction) is 90% or more. As an example, this ratio (i.e., the mole fraction) may be 95% or more.
[0062] The solid electrolyte material of the first embodiment may also consist only of Li, Ti, and F.
[0063] The solid electrolyte material of the first embodiment may also be substantially free of LiF and TiF4.
[0064] "Substantially free of LiF and TiF4" means that a trace amount of LiF and TiF4 is allowed to be mixed in. In this case, the LiF and TiF4 mixed in the solid electrolyte material are less than the detection limit of the X-ray diffraction measurement. The solid electrolyte material of the first embodiment may also be free of LiF and TiF4. According to the above structure, the ion conductivity can be further improved.
[0065] (Second embodiment)
[0066] As described in the [Background Technology] column, Patent Document 1 discloses an electrode active material represented by Li2TiF6. The Li2TiF6 is synthesized by dissolving TiO2 in hydrofluoric acid and finally heat treating it. The synthesis method of this crystal system is a well-known common method. The Li2TiF6 of Patent Document 1 is a trigonal crystal system according to the X-ray diffraction pattern. With regard to the above crystals, there are difficulties in the bonding reliability of the pressed powder structure, for example, it is difficult to achieve practical conductivity when used in a battery. Therefore, the inventors have realized the following second embodiment of the solid electrolyte material.
[0067] Hereinafter, a manufacturing method according to the second embodiment will be described.
[0068] The method for producing a solid electrolyte material of the second embodiment includes: (A) synthesizing a compound containing a crystal phase containing Li, Ti, and F; and (B) performing a treatment of disturbing crystals of the compound.
[0069] According to the above-mentioned production method, a solid electrolyte material having high ion conductivity can be realized. In addition, the solid electrolyte material is excellent in particle deformability and bonding interface formation properties, particularly suitable for a compacted powder structure.
[0070] Hereinafter, the above (A) will be described as a "first step", and the above (B) will be described as a "second step".
[0071] Figure 1 This is a flowchart showing an example of the manufacturing method according to the second embodiment.
[0072] like Figure 1 As shown in FIG. 1 , the manufacturing method of the first embodiment includes a first step S100 and a second step S200 . The second step S200 is performed after the first step S100 .
[0073] In the first step S100 , a compound including a crystal phase containing Li, Ti, and F is synthesized.
[0074] In the second step S200 , a process of disturbing the crystals of the compound synthesized in the first step S100 is performed.
[0075] The “treatment of disturbing the crystals of the compound” includes a treatment of deforming the crystals of the compound and a treatment of causing the crystals of the compound to contain an amorphous structure.
[0076] According to the above configuration, a solid electrolyte material having high ion conductivity can be obtained. The solid electrolyte material contains amorphous material.
[0077] Hereinafter, the first step S100 and the second step S200 will be described in detail.
[0078] (First Step S100)
[0079] In the first step S100, a compound containing a crystal phase including Li, Ti, and F is synthesized. The compound has a composition represented by Li2TiF6, for example. The compound may be crystalline.
[0080] First, raw materials containing constituent elements of the target compound are mixed.
[0081] The raw materials are, for example, fluorides containing Li and fluorides containing Ti, specifically, LiF and TiF4.
[0082] In the case of synthesizing a compound containing a crystal phase containing Li, Ti, and F, as a raw material, not only fluorides but also oxides or other halides can be used.
[0083] The raw material may be a precursor of a compound composed of Li and F and a precursor of a compound composed of Ti and F.
[0084] The raw material may be a powder. The raw material may have an average particle size of, for example, 0.5 μm or more and 10 μm or less.
[0085] Next, the compound can also be obtained by subjecting the mixture of the raw materials to a solid phase reaction.
[0086] The mixture of raw materials may be subjected to heat treatment (calcination), for example. That is, in the first step S100, the compound may be synthesized by calcining the mixture of raw materials.
[0087] By utilizing calcination for synthesis, the secondary phase of the raw material etc. can be suppressed, and the target compound can be generated with high purity and uniformity. Therefore, the components that hinder ionic conductivity will be reduced. In addition, by controlling the calcination conditions (temperature, time, heating and cooling speed or atmosphere), the reaction deviation can be suppressed, and a uniform crystalline compound can be synthesized in high mass production.
[0088] When a compound containing a crystalline phase of Li, Ti and F is synthesized by firing, for example, a mixed material obtained by uniformly mixing the above raw materials is placed in a heat-resistant container (sagger) made of alumina and fired. If the raw materials are stable in air, firing may also be performed in air.
[0089] In order to exhaust the unnecessary reaction gas in the firing furnace, air can be flowed during firing. In the case where the raw material lacks air stability, firing can be carried out in an inert gas atmosphere such as argon or nitrogen. For example, during the firing process, nitrogen is flowed into the furnace while the reaction gas (water and excess gas components, etc.) is discharged, and firing is carried out for more than 1 hour and less than 20 hours in the temperature range of the solid phase reaction (for example, above 600°C and below 700°C). In this way, by introducing air or an inert gas into the firing furnace and exhausting it, it is possible to prevent unnecessary reaction gas components from remaining in the synthesized compound in the furnace.
[0090] Regarding the introduction of gas into the furnace, it is appropriate to avoid the inflow of gas directly facing the sagger containing raw materials. For example, a plate larger than the gas inlet is placed between the gas inlet and the sagger. The thickness of the plate can be any thickness that will not be damaged by the flow or operation of the gas. For example, it is also possible to partially shield it to the extent of erecting a plate such as an alumina plate. In this way, by shielding between the gas inlet and the sagger, the gas can bypass the shielding plate and then contact the sagger. By making the gas bypass and indirectly contact the sagger like this, the following problem can be reduced: the temperature distribution in the sagger becomes larger due to the lower temperature of the part directly facing the gas. As a result, the distribution of the progress state of the synthesis reaction is suppressed from becoming uneven (that is, the deviation of the progress state).
[0091] The gas inlet is preferably arranged at the bottom side of the furnace, and the exhaust port is preferably arranged at the upper side (e.g., the top plate side or the upper side of the side wall). Thus, the reaction gas can be smoothly discharged to the outside of the furnace along with the convection flow in the sintering furnace from bottom to top, thereby reducing the mixing of unnecessary components into the compound.
[0092] The introduced gas may be heated and then introduced into the calcining furnace. Thus, the temperature distribution in the sagger can be suppressed from becoming non-uniform. As a result, a more uniform compound can be obtained because the reaction distribution in the sagger can be made uniform.
[0093] The firing temperature can be any temperature at which the target compound is generated. The firing can also be performed at a temperature above the melting point of the target compound. When fired at a temperature above the melting point of the target compound, since the molten state is higher than the solid fluidity, the composition is diffused and a uniform mass can be obtained.
[0094] The firing temperature may be 600° C. to 750° C. The firing time may be 0.5 to 40 hours. In order to prevent residual raw materials, the temperature, time and exhaust time of the reaction gas required for synthesizing the target compound may be arbitrarily determined. For example, the firing time may also be adjusted according to the amount of powder to be fired.
[0095] In order to uniformly carry out solid phase reaction and crystallization, the heating rate is preferably gradually increased from the reaction start temperature (e.g., about 500°C) to the maximum temperature. The heating rate can be, for example, 50°C / h to 250°C / h. In this way, the temperature non-uniformity in the sintering furnace and in the powder can be suppressed. For example, the maximum temperature difference in the powder is within 20°C. As a result, the growth of crystal particles proceeds uniformly, and a compound with uniform crystallinity is synthesized.
[0096] The uniformity of particle growth can be estimated by the spacing of growth fringes observed like tree rings in particle observation under a scanning electron microscope (SEM). For example, in a 1 μm-sized particle, fringes with a spacing of 0.05 μm to 0.2 μm can be observed.
[0097] The temperature may be further raised after being maintained at 470°C to 530°C for 0.5 to 4 hours around the reaction starting point, for example. This allows the reaction to proceed more uniformly throughout the powder. As a result, the remaining raw materials and composition changes are suppressed, and a uniform compound with good crystallinity can be synthesized.
[0098] The reaction starting point can be confirmed by thermogravimetric differential thermal analysis (TG-DTA) of the mixed powder and observation of the reaction heat. In the case of multiple solid phase reactions, each temperature can be maintained, but as an example, maintaining the reaction at the highest reaction temperature is particularly effective for uniform reaction of the entire powder.
[0099] As the firing furnace, a known atmosphere firing furnace can be used.
[0100] In order to remove the air and moisture between the powder particles deep inside the sagger and completely replace them with inactive gas, inactive gas can be introduced after vacuum replacement. Vacuum replacement can be repeated.
[0101] When the sintering is performed at a temperature above the melting point of the synthesized compound, the sagger used is, for example, a heat-resistant container such as an airtight, dense alumina container. For example, it can be the commonly used SSA-H (purity 95%, density 3.9 g / cm 3, water absorption rate 0%) or above. Thus, synthesis can be performed without allowing the molten component to penetrate the wall surface of the sagger. In addition, since the heat conductivity of this grade of sagger is as high as about 20W / mk, the inhomogeneity of the temperature distribution in the sagger can be suppressed, which is suitable for uniform reaction. In addition, since there is no reaction with the sagger, the compound synthesized in the state of molten block can be easily peeled off from the sagger, so the block of the compound can be recovered with reduced loss.
[0102] The material of the sagger may not be alumina. For example, any refractory material having a high thermal conductivity equal to or higher than that of alumina and a material that is difficult to react with the compound may be used. By using a high thermal conductivity refractory material for the sagger, the inhomogeneity of the temperature distribution in the sagger can be reduced for synthesis.
[0103] Other examples of the material of the sagger include SSA-S, SSA-T, or SSA-995 grades of alumina and high thermal conductivity refractory such as SiC having a thermal conductivity of approximately 17 W / mk.
[0104] In the firing, a sagger may not be used. For example, heat treatment may be performed by spraying powder as in a rotary kiln or spray drying.
[0105] In the first step S100, the raw material mixture may be fired twice. Thus, the deviation of the composition or crystallinity may be reduced. As a result, the solid phase reaction may be carried out more uniformly. The two firings may be performed under different conditions. For example, in order to make the composition more uniform or to prevent the raw material from remaining, the temperature of the second firing may be higher than the temperature of the first firing. In order to improve the crystallinity, the temperature of the second firing may also be lower than the temperature of the first firing. Thus, local deformation (amorphous components) may be removed. Firing after the third firing may also be performed.
[0106] When a compound is synthesized by calcining a raw material mixture, the mass change rate of the compound before and after calcining may be 1% or less. The mass change rate of the compound before and after calcining refers to the percentage of the absolute value of the difference between the mass of the raw material mixture before calcining and the mass of the compound obtained after calcining relative to the mass of the raw material mixture before calcining.
[0107] The synthesis method of the compound containing Li, Ti and F may also be a mechanochemical method instead of calcination. That is, the compound can be synthesized by a reaction performed by mechanochemical treatment. For example, the raw material is placed in a planetary ball mill or a pot ball mill together with a pulverizing medium such as a zirconia ball, and pulverized. By repeatedly performing the reaction under the impact of the pulverizing medium and under an appropriate stress that can maintain crystallinity, a crystalline compound is synthesized. Because it is synthesized in a confined space, the composition will not evaporate, and the raw materials placed in the container can be fully recovered, so it is easy to obtain a material of the feed composition.
[0108] In the case where the mechanochemical treatment is too strong, a compound with low crystallinity can be synthesized. It can also be used as a raw material to implement the first step and the second step. That is, a compound with low crystallinity synthesized by a reaction using a mechanochemical treatment can be used as a raw material to implement the first step and the second step. Thus, the low crystallinity compound synthesized by a reaction using a mechanochemical treatment has a reduced composition deviation during the calcination process and its crystallinity is also improved.
[0109] The pulverizing medium may be a known partially stabilized zirconia. Partially stabilized zirconia has excellent wear resistance. By using partially stabilized zirconia as the pulverizing medium, synthesis can be performed with reduced impurities mixed in due to wear.
[0110] A grinding medium is placed in a mill container in an amount of 10% to 60% of the volume of the container, and after sealing with an inert gas (nitrogen, argon, etc.), the mill is rotated to stir.
[0111] Mechanochemical treatment can also be carried out in air if the raw materials are air-stable.
[0112] The shape of the pulverizing medium may be, for example, a spherical shape with a diameter of 2 mm to 30 mm. The pulverizing properties (for example, synthesis rate) may be appropriately adjusted, and various media sizes may be used.
[0113] In order to improve the crushing property (e.g., synthesis rate), the inner wall of the ball mill can also be made of the same material as the hard crushing medium such as zirconium oxide. The shape of the inner wall can be cylindrical or polygonal such as rectangular. In the case where the inner wall of the ball mill is a polygonal cylindrical shape, the crushing property is enhanced and the synthesis rate is accelerated. Therefore, the processing can be carried out in a shorter time.
[0114] The mechanochemical treatment time is, for example, 1 hour to 80 hours, and generally 10 hours to 20 hours.
[0115] The ball mill can also be heated from the outside to activate the reaction and increase the synthesis rate. For example, it can be heated from 40°C to 60°C. This allows synthesis in a shorter time, so mass productivity is excellent.
[0116] In the case of using raw materials with high mechanochemical activity, the synthesis can be carried out only by the shear stress of the mortar and pestle. In this case, the mechanochemical treatment can be carried out by an automatic mortar (such as a pestle) or manually. The mortar can also be heated to increase the synthesis rate. The reaction temperature can also be managed to stabilize the synthesis state. For example, the mortar can be placed on a hot plate for experimental mixing.
[0117] The crystal contained in the compound synthesized in the first step S100 may be a monoclinic crystal or a tetragonal crystal.
[0118] It should be noted that, for example, if Li2TiF6 in a stoichiometric ratio is synthesized by a general sintering method, a tetragonal crystal can be obtained.
[0119] By deforming the crystallinity in the second step S200, the ion conductivity can be improved. It is believed that the introduction of amorphous properties reduces the binding effect of F ions with high electronegativity on Li ions, thereby improving the ion conductivity.
[0120] The synthesized compound may be a molten body, a sintered body, or a block solidified after powder solidification. The block solidified after powder solidification is easy to work with and has good productivity.
[0121] The composition ratio of the compound containing Li, Ti and F may not be a stoichiometric ratio, and may not be a stoichiometric ratio of Li:Ti:F=2:1:6. In addition, the compound may also contain elements other than Li, Ti and F (i.e., accessory components). Examples of accessory components are Ni, Mo, Cr, Fe and ZrO2. The content of the accessory components may be, for example, 0.01% to 3% by mass relative to the compound, or 0.01% to 3% by mass relative to Li, Ti and F. Such accessory components act as promoters of solid phase reactions, and can cause the reaction to proceed uniformly and in a shorter time or at a lower temperature. Therefore, a solid electrolyte material with high ionic conductivity can be obtained with high synthesis efficiency. In addition, the synthesis energy can also be reduced.
[0122] When synthesizing a compound containing the above-mentioned accessory components, the calcination temperature may be lower than when synthesizing a compound consisting only of Li, Ti, and F. When synthesizing a compound containing the above-mentioned accessory components, the calcination temperature may be 550°C to 750°C.
[0123] It can be confirmed by X-ray diffraction measurement that the synthesized compound contains a crystal phase containing Li, Ti, and F. From the X-ray diffraction pattern, a crystal system such as a tetragonal system can be confirmed.
[0124] After the first step, a part of the starting material (such as TiF4 or LiF) may not remain. After the first step, a part of the starting material (such as TiF4 or LiF) may remain. The remaining starting material may be less than the compound containing the crystalline phase containing Li, Ti and F. That is, the compound containing the crystalline phase containing Li, Ti and F may also be synthesized as the main component. In this way, if the small amount of starting material remaining after the first step is less than Li2TiF6, the conductivity will not be greatly reduced.
[0125] (Second step S200)
[0126] In the second step S200, a process is performed to disturb the crystals of the compound synthesized in the first step S100. For example, mechanical stress or impact is applied to the compound obtained in the first step S100. In this way, a non-crystalline state can be formed.
[0127] The treatment for disturbing the crystal is, for example, a mechanochemical treatment. That is, in the second step S200, the compound may be subjected to a mechanochemical treatment. By subjecting the compound containing the crystal to a mechanochemical treatment, a deformed crystal or amorphous property may be introduced. The method of the mechanochemical treatment may also be the same as the mechanochemical treatment described in the first step S100.
[0128] Mechanochemical treatment has less impurities mixed in, suppresses composition deviation, and has good workability and excellent productivity.
[0129] In the first step S100 , when a compound containing Li, Ti, and F is synthesized by a reaction using a mechanochemical treatment, a production device, a medium, and the like used in the synthesis may be used in the second step S200 .
[0130] The mechanochemical treatment may be ball milling. That is, in the second step S200, the compound may be subjected to mechanochemical treatment using a ball mill.
[0131] The mechanochemical treatment in the second step S200 reduces the crystallinity of the powder or particles (particularly the surface region) of the synthesized compound. That is, the mechanochemical treatment in the second step S200 makes the compound amorphous. In particular, the crystallinity of the surface region of the compound as a powder or particle is reduced. The mechanochemical treatment in the second step S200 can be performed in a shorter treatment time than in the case where the compound is synthesized by a reaction using the mechanochemical treatment in the first step S100, and can also be performed under conditions of small crushing or impact energy.
[0132] Specifically, compared with the mechanochemical treatment in the first step S100, the amount of the pulverizing medium can be reduced, and the amount of the powder fed can be increased. Therefore, compared with general mechanochemical synthesis, the equipment is simpler, and thus the productivity is excellent.
[0133] For example, a zirconia container is used, and zirconia balls are placed in an amount of 10% to 60% of the container volume for mechanochemical polishing. Zirconia balls with diameters of 1 mm to 30 mm are generally used, but may be smaller or larger than this.
[0134] In order to control the mechanochemical action (eg, to reduce it to avoid excess), the pulverizing media may be light in specific gravity, such as alumina-based pulverizing balls.
[0135] In order to prevent the pulverized medium from sticking to the inner wall of the container, an additive that does not adversely affect the properties of the solid electrolyte material may be added. The additive may be a substance that can be removed by drying. An example of the additive is ethanol.
[0136] In order to reduce the internal heating caused by strong impact and friction, the container used for mechanochemical treatment can be small. For example, mechanochemical treatment can use a common ball mill that uses a pot mill, which is most commonly used in the mass production process of ceramic pulverization. Containers of various capacities ranging from tens of milliliters to hundreds of liters can be used, and compounds ranging from a few grams to hundreds of kilograms can be treated.
[0137] According to the manufacturing method disclosed herein, a solid electrolyte material having high conductivity can be synthesized in a short time while suppressing the composition variation of easily evaporated components such as Li. For example, the composition variation can be suppressed to be below -0.01 mass % to 1 mass % (mass ratio of powder before sintering) relative to the mass of the raw material powder.
[0138] The introduction of the amorphous component in the second step can be confirmed from an X-ray diffraction pattern obtained by powder X-ray diffraction measurement.
[0139] As the mechanochemical treatment in the second step S200 is prolonged, the softness of the powder particles can be increased. That is, the crystallinity can be reduced. It should be noted that the softness of the powder particles can be evaluated by microscopic Vickers evaluation of each particle or pressed powder structure to make a relative comparative evaluation of the change in crystallinity. In addition, the softness of the powder particles can also be confirmed by visually observing the changes in the powder properties during the entire manufacturing process. This is because, as the mechanochemical treatment time is prolonged, the change in crystallinity, that is, the softness of the powder particles, increases, and the amount of powder attached to the inner wall of the ball mill container and the zirconia balls, for example, also increases accordingly.
[0140] (other)
[0141] The method for producing a solid electrolyte material according to the second embodiment may further include finely pulverizing the compound after the second step S200. Hereinafter, finely pulverizing the compound is referred to as a "finely pulverizing step."
[0142] In the fine pulverization process, zirconia beads of 1 mm φ or less can also be used as pulverization media for stirring milling. In this process, for example, the solid electrolyte material can be in the form of particles with a particle size of 1 μm or less. In addition to reducing the particle size, amorphous particles are formed on the particle surface. As a result, the obtained solid electrolyte material can be used as a thin layer of solid electrolyte layer, for example.
[0143] When the compound is synthesized by calcination in the first step S100, the calcined product obtained includes a state in which the particles are necked together, i.e., a state in which the particles are bonded, in a solid phase reaction between the contacting particles. Here, the size of the necked agglomerated and consolidated particles is mainly 1 μm to 10 μm. In addition, in a crystalline state in which the anions F with high electronegativity and strong Li ion confinement effect are arranged in an orderly manner, the particle size is, for example, less than 1×10 -9 Therefore, when using it as a solid electrolyte material, the necked agglomerated and consolidated particles are crushed by pulverization or the like, and a treatment to disturb the crystallinity, i.e., the second step, is performed.
[0144] Example
[0145] Hereinafter, the present disclosure will be described in more detail with reference to examples.
[0146] Solid electrolyte materials of samples 1 to 11 were prepared. Samples 1 to 3 correspond to comparative examples, and samples 4 to 11 correspond to examples. Regarding samples 1 to 3, the preparation of the solid electrolyte material does not include synthesis of a compound containing a crystal phase containing Li, Ti, and F. Hereinafter, this example will be described in detail.
[0147] <Sample 1>
[0148] As raw materials, LiF and TiF4 powders with high chemical purity were prepared and weighed at a temperature of 22°C to 26°C and in air with a humidity of about 30% to 50% in such a manner that the raw material powders had a composition ratio shown in Li2TiF6, i.e., a molar ratio of LiF:TiF4 = 2:1.
[0149] Using an alumina porcelain mortar, the prepared raw material powders were mixed with a pestle for about 10 minutes to achieve uniformity to obtain a mixed powder.
[0150] The mixed powder and 15 mm zirconia balls (about 1000 g) were placed in a 1 L cylindrical ball mill container with a zirconia inner wall, and ball milled at a rotation speed of 60 rpm to 80 rpm at room temperature for 3 hours. Then, the processed powder was taken out from the ball mill container. In this way, the solid electrolyte material of sample 1 was obtained.
[0151] <Samples 2 and 3>
[0152] A solid electrolyte material of Sample 2 was obtained in the same manner as Sample 1 except that the ball milling time was changed to 7 hours.
[0153] A solid electrolyte material of Sample 3 was obtained in the same manner as Sample 1 except that the ball milling time was changed to 12 hours.
[0154] <Sample 4>
[0155] (First process)
[0156] First, as starting materials, powders of LiF and TiF4 with high chemical purity were prepared. Then, they were weighed at a temperature of 22°C to 26°C and in air with a humidity of about 30% to 50% in such a manner that the composition after synthesis became the composition ratio shown in Li2TiF6, that is, at a molar ratio of LiF:TiF4=3:1.
[0157] Then, using an alumina porcelain mortar, the powders of the above starting materials were mixed with a pestle for about 10 minutes to achieve uniformity to obtain a mixed powder. The obtained mixed powder (about 5 g) was added to a high-purity (SSA-H) alumina sagger (diameter 40 mm, height 45 mm). In order to prevent the components from evaporating due to firing, a high-purity (SSA-H) alumina lid was placed to seal it.
[0158] Next, in order to improve the temperature uniformity, firing is performed in the central part of the firing furnace. Three pillars (i.e., brackets) are placed under a sagger so that the sagger floats from the bottom of the furnace. The bracket is made of mullite and has a porosity of about 20% and a small heat capacity. Thus, the heater heat (i.e., radiant heat) and inactive gas can also surround the bottom of the sagger. The dimensions of the bracket are 10 mm long, 11 mm wide, and 10 mm high.
[0159] After closing the door of the firing furnace and sealing it, nitrogen is allowed to flow in from the inlet at the bottom of the furnace at a rate of 1L / min to 3L / min, and is discharged from the exhaust port on the upper side of the top plate, and nitrogen is continuously introduced until the firing is completed. In this way, by allowing the gas to flow from the bottom of the furnace to the top plate, even if unnecessary evaporation components or dust in the furnace are generated, the unnecessary components and dust can be discharged to the outside of the furnace along with convection. In this way, impurities mixed into the fired sample can be reduced. In addition, an alumina plate with a thickness of 3mm is placed near the midpoint between the gas inlet and the sagger, and a partial shielding is performed to prevent the gas from being introduced directly to the sagger. It should be noted that the distance between the gas inlet and the sagger is about 10cm.
[0160] The sintering conditions were as follows: the temperature was raised to 500°C at a rate of 100°C / h, then maintained at 500°C for 2 hours, then raised to 600°C at 200°C / h, and maintained for 4 hours. Then, the temperature was cooled to room temperature at a rate of about 200°C / h. It should be noted that the temperature is the actual temperature in the sagger.
[0161] The mass reduction rate after firing was about 0.1% to 1.0% by mass, and evaporation was almost suppressed. Therefore, it can be considered that the composition is consistent with the raw materials.
[0162] In this way, a block-shaped fired product formed by solidifying the powder is obtained.
[0163] (Second process)
[0164] In air, the sintered product (about 5 g) in the sagger was pre-crushed to about 10 μm using an alumina porcelain mortar and pestle. Next, the coarsely crushed sintered product and a 15 mm zirconia ball mill (about 1000 g) were added to a 1-liter cylindrical ball mill container with a zirconia inner wall, and ball milling was performed for 3 hours at a rotation speed of 60 to 80 rpm and room temperature. Then, the treated powder was taken out from the ball mill container.
[0165] As described above, the solid electrolyte material of Sample 4 was obtained.
[0166] <Samples 5 to 7>
[0167] A solid electrolyte material of Sample 5 was obtained in the same manner as Sample 4 except that the ball milling time was changed to 7 hours.
[0168] A solid electrolyte material of Sample 6 was obtained in the same manner as Sample 4 except that the ball milling time was changed to 12 hours.
[0169] A solid electrolyte material of Sample 7 was obtained in the same manner as Sample 4 except that the ball milling time was changed to 20 hours.
[0170] <Samples 8 to 10>
[0171] A solid electrolyte material of Sample 8 was obtained in the same manner as Sample 7 except that 0.2 mass % of iron powder was further added to the mixed powder fired in the first step and the firing temperature for 4 hours in the first step was set to 550° C.
[0172] A solid electrolyte material of Sample 9 was obtained in the same manner as Sample 7 except that 0.1 mass % of chromium powder was further added to the mixed powder fired in the first step and the firing temperature for 4 hours in the first step was set to 550° C.
[0173] A solid electrolyte material of Sample 10 was obtained in the same manner as Sample 7 except that 1 mass % of zirconium oxide was further added to the mixed powder fired in the first step and the firing temperature for 4 hours in the first step was set to 550° C.
[0174] <Sample 11>
[0175] A solid electrolyte material of Sample 11 was obtained in the same manner as Sample 7 except that the calcination temperature for 4 hours in the first step was set to 750°C.
[0176] (Sample Evaluation)
[0177] The crystal phase and ion conductivity of the sample after the first step and the sample after the second step were evaluated. The evaluation results after the first step are shown in Table 1. The evaluation results after the second step are shown in Table 2.
[0178] Regarding the evaluation of the crystalline phase, first, the obtained sample is evenly crushed in an alumina mortar. For example, it is crushed to a degree where coarse particles cannot be felt by touch, for example, it is crushed to a powder with an average particle size of less than 3 μm. Next, the crystalline phase is evaluated by powder X-ray diffraction measurement (XRD). An X-ray diffractometer (MiniFlex600 manufactured by RIGAKU) is used in the measurement. Cu-Kα rays (wavelength and ) as the X-ray source.
[0179] When multiple crystal phases are observed, the crystal phase columns in Tables 1 and 2 are listed in descending order of the intensity of the strongest peak in the X-ray diffraction pattern. The phase listed on the far left is regarded as the main component in the material.
[0180] Regarding the ionic conductivity of the sample, the powder of the sample is placed in a mold (diameter 10 mm), and a uniaxial hydraulic press is used to calculate the ionic conductivity based on the area, thickness, and room temperature impedance characteristics of the compressed powder in the compressed powder sample obtained by applying a pressure of about 3 t / cm. The impedance is measured at room temperature under pressure. It should be noted that the impedance is measured at a measurement frequency of 10 Hz to 10 MHz, a measurement voltage of 1 Vrms, and no DC bias. The deviation of the electrical length of the cable and the measuring fixture is evaluated as the offset.
[0181] Table 1
[0182]
[0183] Table 2
[0184]
[0185] (Inspection)
[0186] When the first step is omitted and the mixture of LiF and TiF4 is ball-milled without synthesizing Li2TiF6 as in samples 1 to 3, the ion conductivity of the solid electrolyte material is lower than that of the example.
[0187] Samples 1 to 3 did not contain amorphous materials containing Li, Ti and F. Although not shown in Table 1, even if the ball milling treatment was continued for more than 100 hours for Sample 3, the ion conductivity did not reach 0.5 μS / cm.
[0188] Therefore, it is difficult to obtain the solid electrolyte material of the present disclosure by omitting the first step and performing the second step only by ball milling (for example, on a scale of several grams to several hundred kilograms).
[0189] Figure 2 It is a graph showing the X-ray diffraction pattern of samples 4 to 7. As shown in samples 4 to 11, in the first step, by sintering under appropriate conditions, the sintered product after the first step becomes a single phase of crystalline Li2TiF6. That is, LiF and TiF4 are not observed in the X-ray diffraction pattern. The crystal is a tetragonal system. It should be noted that, although not shown in Table 1, the ionic conductivity of samples 4 to 11 after the first step and before the second step is the same as the ionic conductivity of samples 1 to 3 as a mixture of raw material powders before the second step.
[0190] Regarding samples 4 to 11, after the second step, in the X-ray diffraction pattern containing a large amount of amorphous materials that appears by disturbing the Li2TiF6 crystals, very wide peaks can be observed. Specifically, for the characteristic X-rays of CuKα, peaks in the range of diffraction angles 2θ of 20° to 22° (i.e., the first range), peaks in the range of 40° to 42° (i.e., the second range), and peaks in the range of 26° to 28° (i.e., the third range) can be observed. Hereinafter, the strongest peak in the first range is referred to as the first peak, the strongest peak in the second range is referred to as the second peak, and the strongest peak in the third range is referred to as the third peak. Figure 2 In the figure, arrows indicate the first peak, the second peak, and the third peak.
[0191] The intensity of the second peak is about 70% to 90% of the intensity of the first peak. The intensity of the third peak is about 10% to 30% of the intensity of the first peak. Therefore, the first peak has a higher intensity than the second peak, and the second peak has a higher intensity than the third peak.
[0192] It should be noted that since the second peak and the third peak overlap, their half-peak widths cannot be accurately calculated. Therefore, the crystallinity is evaluated based on the half-peak width of the first peak. The half-peak widths of the first peaks of samples 4 to 11 are greater than 1°.
[0193] As described above, excellent ion conductivity can be obtained by having disordered Li2TiF6 crystals, that is, amorphous materials.
[0194] On the surface of the crystalline Li2TiF6 powder particles obtained in the first step, there is no region having softness (deformability) provided by disturbing the crystallinity. Therefore, the inter-particle bonding of the pressed powder structure is low, and peeling is easily caused during hot and cold cycles. By the second step, amorphous Li2TiF6 containing soft and deformable crystals is formed on the particles, and a highly reliable conductivity, for example, higher than 1μS / cm, can be obtained in the pressed powder structure.
[0195] After sintering, i.e., after the first step, the half-peak width of the peak corresponding to the first peak of crystalline Li2TiF6 of samples 4 to 11 is 0.4° to 0.6°. Therefore, when the half-peak width of the first peak exceeds 0.6°, it can be said that amorphous Li2TiF6, i.e., amorphous Li2TiF6 is contained.
[0196] As shown in Table 2, the solid electrolyte material having the highest electrical conductivity is Sample 10, and the half-value width of the first peak is 2.13°.
[0197] The peak shape with an extremely wide half-width indicates that the reflection surface spacing that contributes to diffraction has a wide surface spacing distribution corresponding to the peak width (the surface spacing is different). Therefore, it can be considered that samples 4 to 11 contain components with disordered atomic arrangement and low Li constraint, that is, deformed crystals or amorphous. Crystals containing F ions with high electronegativity generally have a tendency to have a strong constraint effect on Li ions and low ionic conductivity. In contrast, by introducing disorder in the atomic arrangement through the second step, it can be made to contain amorphous components that reduce the constraint of Li ions, that is, deformed crystals or amorphous. As a result, it can be considered that the conductivity will increase. It can be considered that since the area with disordered crystallinity is formed by external stress, it can be formed from the surface of the particle to the inside through repeated impact of ball milling. Therefore, it can be considered that the surface contains more disordered crystallinity or amorphousness than the inside of the particle.
[0198] As described above, it is preferable to synthesize crystalline Li2TiF6 in the first step and then disturb the crystallinity of Li2TiF6 by mechanochemical treatment. In this way, a solid electrolyte material with high reliability and high conductivity can be obtained with high productivity.
[0199] It can be seen from samples 4 to 7 that the ionic conductivity is improved by extending the ball milling time. It can also be seen from the increase in the half-peak width of the first peak that amorphous properties are revealed by ball milling. In this way, the ionic conductivity can be further improved or the treatment time can be shortened by controlling the mechanochemical treatment in the second step.
[0200] Since the sintering temperature of the first step was set to above the melting point of the Li2TiF6 solid solution, the sample melted after sintering. In this way, it was confirmed that a solid electrolyte material with the desired high ion conductivity can also be obtained by performing the second step on the molten crystal (Li2TiF6 solid solution).
[0201] As shown in samples 8, 9 and 10, for the Li2TiF6 solid solution containing Fe, Cr or ZrO2 as a secondary component, even if the sintering temperature is a lower temperature (550°C) than that of samples 4 to 7 of other embodiments, a single phase can be obtained, and the ion conductivity after the second step is as high as more than 1μS / cm. That is, in the case of containing secondary components, it is believed that there is an effect of promoting solid phase reaction and suppressing the starting raw materials.
[0202] The solid electrolyte material of this embodiment is synthesized in air and has excellent air stability.
[0203] Industrial Applicability
[0204] The solid electrolyte material disclosed herein can be utilized in secondary batteries such as all-solid-state batteries used in various electronic devices, automobiles, and the like.
Claims
1. A solid electrolyte material, which is a solid electrolyte material containing Li, Ti and F, which contains an amorphous substance containing Li, Ti and F.
2. The solid electrolyte material according to claim 1, wherein The solid electrolyte material is a solid solution.
3. The solid electrolyte material according to claim 1 or 2, wherein in an X-ray diffraction pattern obtained by powder X-ray diffraction measurement of the solid electrolyte material, there is at least one peak in each of a first range where the diffraction angle 2θ is 20° to 22°, a second range where the diffraction angle 2θ is 40° to 42°, and a third range where the diffraction angle 2θ is 26° to 28°, and the half-width of the strongest peak in the first range is 1° or more.
4. The solid electrolyte material according to claim 3, wherein The strongest peak in the first range has a higher intensity than the strongest peak in the second range, and the strongest peak in the second range has a higher intensity than the strongest peak in the third range.
5. The solid electrolyte material according to claim 1, wherein The solid electrolyte material is in a particle form.
6. The solid electrolyte material according to claim 5, wherein The crystallinity of the surface of the solid electrolyte material is lower than the crystallinity of the central portion of the solid electrolyte material.
7. The solid electrolyte material according to claim 1, further comprising at least one selected from the group consisting of Ni, Mo, Cr, Fe and ZrO2. The solid electrolyte material according to claim 1 , further comprising a crystal phase containing Li, Ti and F.
9. The solid electrolyte material according to claim 8, wherein The crystal phase contains tetragonal crystals.
10. A method for producing a solid electrolyte material, comprising: (A) synthesizing a compound containing a crystal phase containing Li, Ti, and F; and (B) performing a treatment of disturbing crystals of the compound.
11. The method for producing a solid electrolyte material according to claim 10, wherein: In the above (A), the compound is synthesized by calcining a mixture of raw materials.
12. The method for producing a solid electrolyte material according to claim 11, wherein: In the calcination, the mass change rate of the compound before and after the calcination is 1% or less.
13. The method for producing a solid electrolyte material according to claim 10, wherein: In said (B), said compound is subjected to a mechanochemical treatment.
14. The method for producing a solid electrolyte material according to claim 13, wherein: The mechanochemical treatment is ball milling.
Citation Information
Patent Citations
Fluoride electrode active material
JP2009238687A